CHOICE AND STUDY OF BASE FOR PRODUCTION OF SUPPOSITORIES WITH ANTIHISTAMINIC ACTION - N. V. Prokuschenko; E. T. Zhilyakova (Фармация и фармакология (Пятигорск), 2015)
Russian pharmaceutical industry development is made possible by new medicinal forms production. To widen the assortment of antihistaminic drugs we have offered a model mixture of suppositories